The COVID-19 pandemic: An opportunity to rethink and harmonise the frequency of follow-up visits for patients with early stage breast cancer. (June 2021) - Surujballi, Julian; Shah, Hely; Hutton, Brian; Alzahrani, Mashari; Beltran-Bless, Ana-Alicia; Shorr, Risa; Larocque, Gail; McGee, Sharon; Cole, Katherine; Ibrahim, Mohammed F.K.; Fernandes, Ricardo; Arnaout, Angel; et al.
Highlights: Decreased follow-up frequency in patients with early breast cancer does not harm quality of life. Follow-up on-demand does not decrease quality of life. Decreased follow-up frequency improves cost-effectiveness. Abstract: Purpose: While routine, in-person follow-up of early-stage breast cancer patients (EBC) after completion of initial treatment is common, the COVID-19 pandemic has resulted in unprecedented changes in clinical practice. A systematic review was performed to evaluate the evidence supporting different frequencies of routine follow-up. Methods: MEDLINE and the Cochrane Collaboration Library were searched from database inception to July 16, 2020 for randomized controlled trials (RCTs) and prospective cohort studies (PCS) evaluating different frequencies of routine follow-up. Citations were assessed by pairs of independent reviewers. Risk of Bias (RoB) was assessed using the Cochrane RoB tool for RCTs and the Newcastle-Ottawa Quality Assessment Scale for Cohort Studies. Findings were summarized narratively. Results: The literature search identified 3316 studies, of which 7 (6 RCTs and 1 PCS) were eligible. Study endpoints included; quality of life (QoL; 5 RCTs and 1 PCS), disease free survival (DFS) (1 RCT), overall survival (OS) (1 RCT) and cost-effectiveness (1 RCT). The results showed reduction in follow-up frequency had no adverse effect on: QoL (6 studies, n = 920), DFS (1 trial, n = 472) or OS (1 trial, n = 472), but improved cost-effectiveness (1 trial, n = 472). Four RCTs specifically examined follow-up on-demand versus scheduled follow-up visits and found no statistically significant differences in QoL (n = 544). Conclusion: While no evidence-based guidelines suggest that follow-up of EBC patients improves DFS or OS, routinely scheduled in-person assessment is common. RCT data suggests that reduced frequency of follow-up has no adverse effects.